PENGARUH PERBAIKAN TANAH DENGAN MENGGUNAKAN METODE GROUTING SEMEN TERHADAP DAYA DUKUNG PADA PASIR LEPAS DI DAERAH PANTAI BUNGUS - Muhammad Fahrul Razif; Andriani; Abdul Hakam (Racic : Rab Construction Research, 2025)
Padang City has numerous coastal areas with sandy soil layers that extend up to 32 m deep. In general, sandy soil in coastal areas consists of loose sand that has low shear strength. Sand in loose conditions needs to be improved to increase its bearing capacity. Bungus Beach is a coastal area in Padang City, West Sumatra. In this study, cement grouting was conducted to enhance the bearing capacity of loose sand on the Bungus beach sand. Grouting was carried out using a 1:1 cement-to-water mixture and with curing times of 1 day, 3 days, and 7 days. Sondir tests were also conducted to obtain soil classification in the field and cone resistance values (qc) before and after grouting. Based on the results of this study, there was an increase in the QC value after grouting by 1.33 - 2.33 times from the QC value before grouting at a distance of 1D (10 cm) at a depth of 100 cm with a maximum curing time of 7 days, while at a distance of 4D the QC value only increased by 1.20 - 2.00 times from the QC value before grouting. The QC value decreases if the distance between the sounding point and the grouting point is far.